CAD software package for noise reduction in MCM layout design - Khoo, Nai Chuan. (2008)
The aim of this project is to develop a window based software that simulates or predicts noise performance in a multi-chip module. The analysis results would allow development of techniques to reduce the noises. CAD packages would subsequently be developed using these techniques for the optimisation of noise reduction in a MCM layout design. The software is developed using Microsoft Visual Basic 6.0. The software development can be divided into two parts. The purpose of the first part is to generate or capture layout and routing information of a multi-chip module. Routing information is stored on file in the form of routing co-ordinates or nodes.